2018
DOI: 10.1002/ijc.31848
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of red and processed meat and breast cancer incidence: A systematic review and meta‐analysis of prospective studies

Abstract: Prior studies on red and processed meat consumption with breast cancer risk have generated inconsistent results. We performed a systematic review and meta-analysis of prospective studies to summarize the evidence regarding the relation of red meat and processed meat consumption with breast cancer incidence. We searched in MEDLINE and EMBASE databases through January 2018 for prospective studies that reported the association between red meat and processed meat consumption with incident breast cancer. The multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 42 publications
3
55
0
5
Order By: Relevance
“…To the best of our knowledge, four cohort studies 25,27,35,39,40 and one pooled case-control analysis 31 examined meat consumption and breast cancer risk by ER status with most finding no significant differences by ER status. 5 Our findings are consistent with past literature as we found that there was no significant heterogeneity in meat-associated breast cancer risk by ER status.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…To the best of our knowledge, four cohort studies 25,27,35,39,40 and one pooled case-control analysis 31 examined meat consumption and breast cancer risk by ER status with most finding no significant differences by ER status. 5 Our findings are consistent with past literature as we found that there was no significant heterogeneity in meat-associated breast cancer risk by ER status.…”
Section: Discussionsupporting
confidence: 93%
“…Anderson et al reported no association between red meat consumption and breast cancer risk in a meta-analysis of 11 prospective cohorts, whereas Farvid et al reported borderline significant positive associations between red meat consumption and breast cancer risk in a meta-analysis of 13 cohort, 3 nested case-control and 2 clinical trial studies. 4,5 An association between red meat and breast cancer may be due to dietary heme iron, fat and N-glycolylneuraminic acid as these compounds found in red meat are indicated to possibly increase tumor formation. 6 However, we did not find significant association between quartiles of heme iron and breast cancer risk in the present study (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive consumption of meat and animal products may be deleterious to human health (with meta-analytic evidence regarding cancer [1][2][3][4], cardiovascular disease [5][6][7], metabolic disease [8][9][10], obesity [11], stroke [12], and all-cause mortality [13], albeit sometimes subject to methodological limitations), promotes the emergence and spread of antibiotic-resistant pathogens [14], is a major source of greenhouse gas emissions and environmental degradation [15], and contributes to market demand for industry practices that cause the preventable suffering of more than one billion animals in the USA annually [16]. Therefore, developing simple, effective interventions to reduce meat consumption could carry widespread societal benefits.…”
Section: Introductionmentioning
confidence: 99%